Spherical tokamak Globus-M2: design, integration, construction. (9th May 2017) - Minaev, V.B.; Gusev, V.K.; Sakharov, N.V.; Varfolomeev, V.I.; Bakharev, N.N.; Belyakov, V.A.; Bondarchuk, E.N.; Brunkov, P.N.; Chernyshev, F.V.; Davydenko, V.I.; Dyachenko, V.V.; Kavin, A.A.; et al.
Abstract: The Globus-M spherical tokamak has demonstrated practically all of the project objectives during the 15-year period of operation. The main factor limiting further progress in plasma performance is a relatively low toroidal magnetic field. The maximum toroidal magnetic field achieved on Globus-M was 0.4 T with the exception of a limited number of shots with 0.55 T, which led to damage of the toroidal field coil in 2002. The increase of the magnetic field up to 1.0 T together with the plasma current up to 0.5 MA will result in the significant enhancement of the operating parameters in the upgraded Globus-M2 machine. The experimental program will be focused on plasma heating and non-inductive current drive and will contribute to the creation of a physical and technological base for the compact fusion neutron source development. In the article a brief overview of the physical background for the machine upgrade is outlined. The current status of the project implementation is described. First experimental results on moderate magnetic field increase from 0.4 T up to 0.5 T in the existing Globus-M machine are discussed. The improvement of plasma confinement as well as enhancement of efficiency of the beam driven current is observed.